KARAKTERISTIK PRODUKSI PADI DAN PEMETAAN LUAS LAHAN PANEN MENGGUNAKAN ANALISIS BIPLOT BERDASARKAN DATA PRODUKTIVITAS PADI - Nadabunda Husnul Khotimah; La Zakaria (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Rice plants are food for the people of Indonesia. The availability of productivity data is one of the key instruments in planning and evaluating government policies to increase national rice production. BPS has collected the data and used it as one of the elements in calculating rice production. In order to obtain the characteristics of rice production and mapping the area of rice harvested land in ten provinces of the Indonesian island of Sumatra in 2022 using the biplot analysis method. From the results of the study, it was found that areas with similar characteristics of harvested land area, productivity in ten provinces on the island of Sumatra were relatively varied and production with land area had a fairly high positive correlation